Biodynamic optical assay for embryo viability - Li, Zhe (J Biomed Opt, 2019)
Early stage porcine parthenogenetic embryos were evaluated for metabolic activity using a biodynamic microscope (BDM) that images dynamic light scattering using low-coherence digital holography. The microscope has a 45-deg illumination configuration that reduces specular background for the imaging of small translucent samples. The off-axis illumination is compatible with coherence-gated imaging because of volumetric light scattering in which the coherence plane is tilted at half the illumination angle in a three-dimensional tissue target. The BDM was used to profile the viability of porcine parthenotes with normal and with inhibited mitochondrial adenosine triphosphate (ATP) production using Doppler fluctuation spectroscopy. The ATP concentrations in the parthenotes, which are indicative of developmental potential, were validated by a conventional bioluminescence assay. Biodynamic classifications achieved [Formula: see text] accuracy correlating sample ATP treatment, providing a quick, label-free surrogate measurement to replace invasive metabolic assays as a candidate for evaluating quality of early embryos in the assisted reproductive technology setting.